Role of Echo-Planar Diffusion-Weighted Magnetic Resonance Imaging in Diagnosis of Cholesteatoma - Semra, Kulekci; Cigdem, Kalaycik Ertugay; Sema, Zer Toros; Omer, Cagatay Ertugay; Shahrouz, Sheidaei; Kerem, Sami Kaya; Cagatay, Oysu (Journal of Otolaryngology Advances, 2016)
Objective: We compared preoperative data of physical examination, CT and diffusion MRI findings of temporal bone with our intraoperative observations. We investigated the diagnostic efficiency of single-shot spin echo echoplanar diffusion MRI (SS SE EPI) on primary cholesteatoma. Methods: 33 patients with chronic otitis media who had been admitted to Otolaryngology Department of Haydarpasa Numune Training and Research Hospital between June 2010 and September 2011 were involved in this study. All patients did undergo otoscopic and audiometric examination. After imaging of temporal bone by CT and diffusion MRI, patients were operated and intraoperative observations were recorded. Patients with intraoperatively approved cholesteatoma were defined as group 1 and those without cholesteatoma were defined as group 2. Perioperative and preoperative findings of physical examination, CT and MRI of all patients were compared one by one. Results: Positive physical examination findings have been superior to MRI and CT, having a sensitivity of 96%, specifity of 87.5%, positive predictive value of 96% and negative predictive value of 87.5%. In terms of effectiveness of MRI in diagnosing intraoperative cholesteatoma, we had a sensitivity of 80%, specifity of 50%, positive predictive value of 83.3% and negative predictive value of 44.4%. These values are also lower than previously reported results. Conclusion: When we had preoperative suspection of cholesteatoma on physical examination and diffusion MRI, in addition with bone tissue erosion on CT, we found that physical examination is superior to MRI and CT in terms of capability of diagnosing the disease.